PENGARUH KEPEMIMPINAN, MOTIVASI dan SISTEM PENGHARGAAN TERHADAP KEPUASAN KERJA DI MASA PANDEMI COVID 19 (STUDI KASUS PADA KARYAWAN PT. SEJAHTERA SUNINDO TRADA SEMARANG) - Syauqy Rifqy Muslim (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The purpose of this study is to determine the influence of leadership, motivation, and reward systems on job satisfaction during the COVID-19 pandemic. The respondents of this study were all employees of PT. Sejahtera Sunindo Trada Semarang as many as 88 people. The independent variables in this study were leadership (X1), motivation (X2) and reward system (X3), the intervening variable was job satisfaction. The sampling method used in this study was to distribute online questionnaires through google forms for 7 days. The data analysis techniques used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis T test, F test and R square test. The application used is SPSS version 22. The results of the T test show that the Leadership and Reward System have a positive and significant effect on job satisfaction as evidenced by the t-value of the t-count > t table. While motivation does not have a positive and significant influence on job satisfaction as evidenced by the value of t count < t table. Keywords: Leadership, motivation, reward system, job satisfaction.